Pengembangan Modul Elektronik Berbasis Aplikasi Canva pada Mata Pelajaran PAI-BP SMP Kelas VII - Ikhwan, Khairul; Aspandi, Aspandi; Hidayatullah, Hidayatullah (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2024)
The aim of this research is to determine the stages of developing electronic modules using the Canva application in Islamic subjects and character education for class VII students. The research and development method of the ADDIE model which includes five development stages is used as the research method. The first stage includes analysis of skills, student characteristics and material. The second stage includes material design, electronic module design, and evaluation design. The third stage involves developing and testing electronic modules with teachers, students and PAI colleagues. The fourth stage includes implementation in small groups, while the fifth stage includes formative and summative assessments. The research instruments were expert validation questionnaires and multiple choice tests before and after studying the material. The application used was Canva which was chosen because of its ease of use and combination of images, animation, sound and video.Keyword : Electronic Module; Canva APP; PAI-BP